2020
DOI: 10.1002/fsn3.1760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fatty acid‐related nutritional quality indices in fried and raw nile tilapia, (Oreochromis Niloticus), fish muscles

Abstract: During frying, fat degrade and many reactions occur resulting in numerous altered fatty acid products. This would lead to the formation of Tran's fatty acids and changes in nutritional qualities. Hence, this study was aimed to determine the changes during frying on fatty acid composition of Nile tilapia (Oreochromis Niloticus) fish muscle from local fish market of Hawassa, Ethiopia. Fish fryers reported that they usually use palm oil for frying. They also indicated that the oil is kept for days and reused for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The results show that frying decreased both the saturated and unsaturated fatty acids. This is consistent with the work of Mekonnen et al [47], who reported a decrease in fatty acid content in fish muscle after frying. The decrease in fatty acids might be due to the oxidation of fat during frying.…”
Section: Fatty Acid Compositionsupporting
confidence: 93%
“…The results show that frying decreased both the saturated and unsaturated fatty acids. This is consistent with the work of Mekonnen et al [47], who reported a decrease in fatty acid content in fish muscle after frying. The decrease in fatty acids might be due to the oxidation of fat during frying.…”
Section: Fatty Acid Compositionsupporting
confidence: 93%
“…Therefore, the n–3/n–6 PUFA ratio can be used for the potential cardiovascular (and health) effect of foods. In the present study, the n–3/n–6 PUFA ratios were declining in each oil during heating sequences, in concert with previous findings on the effect of frying on the n–3/n–6 PUFA ratios in different foods and oils [ 51 , 55 , 56 , 68 , 69 , 70 , 74 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 92%
“…Heating decreased the HH ratio in each plant-based oil investigated in the present study. In contrast, a previous study didn’t find lower HH ratio in tilapia after frying [ 70 ], while in mussels the HH ratio was even increased compared to fresh samples [ 80 ]. To the best of our knowledge, no previous studies have investigated the effect of heating on the HH ratio of oils, only in fried foods.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The crispiness of the fried product, the aroma of baking and frying, and the pleasant golden to brown color make fried tilapia a popular food worldwide [ 3 ]. The smell of food is an important index in food evaluation, so the study of fried food is very important [ 4 ].…”
Section: Introductionmentioning
confidence: 99%